Nontrivial solution of third-order nonlinear eigenvalue problems (II) - Zhang, Xinguang; Liu, L. (Elsevier Inc., 2008)
In this paper, we firstly make some corrections for typos errors on our paper ‘‘NontrivialSolution of Third-order Nonlinear Eigenvalue Problems, Appl. Math. Comput. 176(2006),714–721”. And then, we supplement some cases which have not been studied in the abovepaper.